High-field studies of the slow thermal death of interlayer coherence in quasi-two-dimensional metals - Singleton, J; Goddard, P; Ardavan, A; Bangura, A; McDonald, R; Schlueter, J (2006)
The interlayer magnetoresistance sigma(zz) of the organic metal kappa-(BEDT-TTF)(2)Cu(NCS)(2) has been studied in fields B of up to 45 T and at temperatures T from 0.5 K to 50 K. The peak in rho(zz) seen in exactly in-plane fields, a definitive signature of interlayer coherence, remains to Ts exceeding the Anderson criterion for incoherent transport by a factor similar to 25. Angle-dependent magnetoresistance oscillations (AMROs) due to Fermi-surface orbits are suppressed by rising T, with a T-2 dependence suggesting electron-electron scattering.